Lifetime alcohol use among persons living with HIV is associated with frailty. (1st February 2020) - Maffei, Vincent J.; Ferguson, Tekeda F.; Brashear, Meghan M.; Mercante, Donald E.; Theall, Katherine P.; Siggins, Robert W.; Taylor, Christopher M.; Molina, Patricia; Welsh, David A.
Abstract : Background: The average lifespan of persons living with HIV (PLWH) on antiretroviral therapy approximates the general population. However, PLWH are susceptible to early aging and frailty. Behaviors such as alcohol consumption may contribute to frailty among PLWH. Objective: To determine the relationships between recent and lifetime alcohol use and frailty among PLWH. Design: Cross-sectional, prospective cohort study of in-care PLWH ( n  = 365) participating in the New Orleans Alcohol Use in HIV Study. Methods: Recent alcohol exposure was measured by the 30-day alcohol timeline follow-back (TLFB) assessment and by whole-blood-spot phosphatidylethanol (PEth) quantitation. Lifetime alcohol exposure (LAE) was estimated by a modified lifetime drinking history instrument. Frailty was assessed by a 58-item deficit index (DI58) and the phenotypic frailty index (PFI). The Veterans Aging Cohort Study Risk Index 2.0 was calculated. Results: Using generalized linear regression, LAE was positively associated with the DI58 (95% CI 0.001--0.006) and PFI severity (95% CI 0.004--0.023) after adjustment for age and other factors. Conversely, recent alcohol exposure was negatively associated with the DI58 [TLFB 95% CI: (−0.126 to −0.034), PEth: (−0.163 to −0.058)] and PFI severity [TLFB 95% CI (−0.404 to −0.015), PEth (−0.406 to 0.034)]. The VACS was not associated with alcohol use. Median per-decade alcohol exposure peaked in the second decade and tapered with aging thereafter. Increasing LAE and decreasing TLFB were co-associated with a specific subset of health deficits. Conclusion: Lifetime alcohol use is positively associated with frailty among PLWH. Specific health deficits may discourage alcohol consumption in some PLWH. Abstract : Supplemental Digital Content is available in the text